73 Substance P And Its Regulatory Pathway In Response To Glucocorticoides. (5th September 2014) - Mousavizadeh, Rouhollah; Backman, Ludvig; McCormack, Robert G; Scott, Alexander
Abstract : Introduction: Substance P (SP) which is produced by neuronal and non- neuronal cells has various functions. In addition to its role in pain transmission, this neuropeptide has effects on tissue matrix remodelling, cell growth, angiogenesis and inflammation. 1, 2 SP has previously been shown to be correlated to pain levels in tendinopathy. The painful area of rotator cuff tendinosis is correlated with the local tissue level of SP, and also that SP can be endogenously produced by tendon fibroblasts, particularly when these cells are subjected to repetitive mechanical loading. 3 Glucocorticoid injections are frequently used as a treatment for chronic tendinopathy, although clinicians are now increasingly aware of caveats to this approach. 4 Several randomised trials and systematic reviews have demonstrated acute pain-relief in patients with tendinopathy who receive corticosteroid injections, despite the risks of rupture or long-term recurrence of tendon pain 5 . We hypothesise that glucocorticoids reduce the SP production in tendon tissue which subsequently lead to short-term pain relief and decrease in tensile strength of the tendons. Methods: Human tendon fibroblasts were isolated from healthy Achilles or hamstrings tendons of male and female recreational athletes aged between 22–40 (n = 6). Cells were cultured in the presence or absence of dexamethasone (1 to 400 nM), an inhibitor of the glucocorticoid receptor (RU486), recombinant TGF-beta (2.5 or 5.0 ng/ml), or an inhibitor of the TGF-beta receptor (A83.01), recombinant human IL-1β and IL-6. Expression levels of the genes encoding for SP (TAC1) and its preferred receptor (NK1R), IL-1α, IL-1β and IL-6 were determined with qPCR, and protein levels of SP were examined by enzyme immunoassay and Western blot. Results: Exposure of human tendon cells to dexamethasone resulted in a time-dependent reduction of mRNA for SP in both hamstrings and Achilles tenocytes, whereas NK1R was unaffected. SP protein was also substantially decreased by dexamethasone (Figure 1 ). The reduction of SP mRNA was dependent on signalling through the glucocorticoid receptor (Figure 2 ). Dexamethasone also prevented induction of SP by IL-1β and by cyclic mechanical loading (Figure 3 ). Discussion: This study demonstrates that dexamethasone treatment of human tendon fibroblasts reduces the expression of SP through a glucocorticoid receptor-dependent pathway. Given that local fibroblasts contribute to the increased levels of SP in tendinopathy, a reduction of SP by corticosteroids in patients with tendinopathy may contribute pain relief. Drugs interfering with SP signalling could be a future target in the treatment of tendinopathy. References: Andersson G, et al . Regul Pept. 2008;150(13):81–87 Coombes BK, et al . Lancet 2010;376(9754):1751–1767 Fong G, et al . J Orthop Res 2013;31(1):91–98 Gotoh M, et al . J Orthop Res. 1998;16(5):618–621 Metcalfe D. Rheumatology (Oxford). 2008;47:Ii183–Ii184